DAMPAK SAMPAH PLASTIK TERHADAP HEWAN YANG DIREPRESENTASIKAN PADA TUBUH MANUSIA - Maria Paragita Puspita; Arti Wulandari; Syaifudin Iskandar (Specta: Journal of Photography, Arts, and Media, 2021)
The Impact of Plastic Waste on Animals Represented on the Human Body. Expression refers to an artist’s inner feelings, or ideas. In addition to being a medium of expression, photos can be a medium of messaging. The easiest way to describe the intent or message of a photo is making the addition of properties related to the object as a supporting element. The creation of this photo work shows the impact of plastic waste on animal life through visual language on the human body. Plas- tic waste and the human body become very important objects in creation process. Plastic waste is a lightweight and durable object that is no longer used. The human body was chosen to express and represent how harmed and injured animals feel from the impact of plastic waste. Representation is the act of representing, describing or symbolizing objects and/or processes. The result of this photo creation is expected to represent the embodiment of the idea of what if humans feel the same way animals feel because of the impact of plastic waste.ABSTRAKEkspresi merupakan ungkapan batin, perasaan, atau gagasan seorang seniman. Selain menjadi media ekspresi, foto bisa menjadi media penyampaian pesan. Cara yang paling mudah untuk menggambarkan maksud atau pesan dari sebuah foto dengan penambahan properti yang berhubungan dengan objek sebagai elemen pendukung. Artikel ini bertujuan menjabarkan penciptaan karya fotografi yang menampilkan dampak sampah plastik terhadap kehidupan hewan dengan objek tubuh manusia. Sampah plastik dan tubuh manusia menjadi objek penelitian dalam pembuatan karya ini. Metode perwujudan karya yang dilakukan adalah pencarian ide, pemotretan, editing, kurasi foto, penyajian karya foto. Hasil karya memperlihatkan bagaimana tubuh manusia mengekspresikan dan merepresentasikan perasaan hewan-hewan yang mati dan terluka karena dampak sampah plastik.